A review of airborne polycyclic aromatic hydrocarbons (PAHs) and their human health effects - Kim, Ki-Hyun; Jahan, Shamin Ara; Kabir, Ehsanul; Brown, Richard J.C. (Environment international, 2013)
Polycyclic aromatic hydrocarbons (PAHs) are a large group of organic compounds comprised of two or more fused benzene rings arranged in various configurations. PAHs are widespread environmental contaminants formed as a result of incomplete combustion of organic materials such as fossil fuels. The occurrence of PAHs in ambient air is an increasing concern because of their carcinogenicity and mutagenicity. Although emissions and allowable concentrations of PAHs in air are now regulated, the health risk posed by PAH exposure suggests a continuing need for their control through air quality management. In light of the environmental significance of PAH exposure, this review offers an overview of PAH properties, fates, transformations, human exposure, and health effects (acute and chronic) associated with their emission to the atmosphere. Biomarkers of PAH exposure and their significance are also discussed.